Tax Revenue, Domestic Investment, and Economic Growth: Evidence from Private and Public Investment Moderation - Ifeoma Florence Okpalanwabude (Jurnal Ekonomi Manajemen Bisnis dan Akuntansi, 2026)
Fluctuations in the economic growth of developing countries have raised concerns about the effectiveness of tax revenue mobilization and its relationship with domestic investment. This study examines how taxation policy affects economic growth using Jorgenson’s neoclassical investment theory and Laffer’s taxation theory. Economic growth (RGDP) is used as the dependent variable, while corporate income tax revenue (CIT), value-added tax revenue (VAT), private investment, public investment, and macroeconomic control variables serve as explanatory variables. Private and public investments are also treated as moderating variables. The study employs the Autoregressive Distributed Lag (ARDL) model to analyze both short-run and long-run relationships. Diagnostic tests confirm the robustness of the model, including the absence of autocorrelation, homoscedastic residuals, and stability confirmed by the CUSUM test. Empirical results indicate that CIT positively affects GDP (0.308), while VAT has a small negative effect (-0.006). Private investment significantly increases GDP (4.55), with an adjustment speed toward equilibrium of 43%. Overall, stable fiscal policy and effective investment allocation strengthen the relationship between tax revenue and sustainable economic growth.